2017
DOI: 10.3389/fmicb.2017.01735
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology: An Untapped Resource for Food Packaging

Abstract: Food commodities are packaged and hygienically transported to protect and preserve them from any un-acceptable alteration in quality, before reaching the end-consumer. Food packaging continues to evolve along-with the innovations in material science and technology, as well as in light of consumer's demand. Presently, the modern consumers of competitive economies demands for food with natural quality, assured safety, minimal processing, extended shelf-life and ready-to-eat concept. Innovative packaging systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
139
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 292 publications
(143 citation statements)
references
References 251 publications
(292 reference statements)
1
139
0
3
Order By: Relevance
“…Clay and silicates have been also used as nanoparticles in the production of intercalated and exfoliated nanocomposites [75]. The former have a multilayered structure with alternating polymer/filler layers lying apart by few nanometers, while in the latter the filler layers are delaminated and randomly dispersed in the polymer matrix [76].…”
Section: Nanotechnology Application In Active Packagingmentioning
confidence: 99%
“…Clay and silicates have been also used as nanoparticles in the production of intercalated and exfoliated nanocomposites [75]. The former have a multilayered structure with alternating polymer/filler layers lying apart by few nanometers, while in the latter the filler layers are delaminated and randomly dispersed in the polymer matrix [76].…”
Section: Nanotechnology Application In Active Packagingmentioning
confidence: 99%
“…Carbon nanotubes have also been developed in packaging to pump out carbon dioxide or absorb undesirable flavors (Sinha et al 2006). It has been known that CNTs also have antibacterial properties, which may be due to their direct penetration through microbial cells (Sharma et al 2017). It has been reported that antimicrobial activity of silver nanoparticles against E. coli and B. cereus spores is significantly enhanced in combination with titanium dioxide and carbon nanotubes, respectively (Krishna et al 2005).…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…One of the main functions of food packaging is to prevent or lower the moisture transfer between food and surrounding environment. Therefore, a proper gas and water vapour permeation can maintain food quality and improve stability and shelf life . Nanoparticles have been used to fill the empty spaces in the film microstructure and thus prevent the migration of molecules.…”
Section: From Polysaccharide Nanofillers To Nanoengineering Of Chitosanmentioning
confidence: 99%